The Effect of Gallery Walk Cooperative Learning Model on Learning Outcomes in Economics Lessons - Setiawan Z, Roni (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study aims to determine the effect of the cooperative learning model of the gallery walk type on student learning outcomes in class X1 at SMA Negeri 5 Sidrap as well as an overview of student learning outcomes after applying the learning model. Methodology: This study used the Pre-Experimental Research Design The One Group Pretest-Posttest Design with a population of 30 students in class X1 at SMA Negeri 5 Sidrap. Due to the relatively small population size, 100% of the population was taken, so the number of samples in this study were 30 students (one experimental class). Data collection was carried out using questionnaires, tests, observations, and documentation. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Main Finding: The results showed that the gallery walk cooperative learning model had a correlation of 0.782 in the medium category with the simple regression analysis equation Y = -12.507 + 1.641X. The results of the hypothesis test with SPSS obtained tcount = 6.640 and ttable of 2.048 this means arithmetic ≥ ttable with a value of 6.640 ≥ 2.048 with a significance value of 0.000 so that H1 is accepted and H0 is rejected, this shows that the influence of the use of the gallery walk cooperative learning model on results study class X1 students of SMA Negeri 5 Sidrap. The magnitude of the contribution of the influence of the learning model is 61.2%, while 38.8% is influenced by other factors that have not been studied in this study. Novelty/Originality of this study: Gallery walk cooperative learning model in learning activities to improve student learning outcomes.